Simultaneous Near-Infrared Spectroscopy (NIRS) and Amplitude-Integrated Electroencephalography (aEEG): Dual Use of Brain Monitoring Techniques Improves Our Understanding of Physiology - Variane, Gabriel Fernando Todeschi; Chock, Valerie Y.; Netto, Alexandre; Pietrobom, Rafaela Fabri Rodrigues; Van Meurs, Krisa Page (Frontiers in Pediatrics, 2020)
Continuous brain monitoring tools are increasingly being used in the neonatal intensive care unit (NICU) to assess brain function and cerebral oxygenation in neonates at high risk for brain injury. Near infrared spectroscopy (NIRS) is useful in critically ill neonates as a trend monitor to evaluate the balance between tissue oxygen delivery and consumption, providing cerebral and somatic oximetry values, and allowing earlier identification of abnormalities in hemodynamics and cerebral perfusion. Amplitude-integrated electroencephalography (aEEG) is a method for continuous monitoring of cerebral function at the bedside. Simultaneous use of both monitoring modalities may improve the understanding of alterations in hemodynamics and risk of cerebral injury. Several studies have described correlations between aEEG and NIRS monitoring, especially in infants with hypoxic ischemic encephalopathy (HIE), but few describe the combined use of both monitoring techniques in a wider range of clinical scenarios. We review the use of NIRS and aEEG in neonates and describe four cases where abnormal NIRS values were immediately followed by changes in brain activity as seen on aEEG allowing the impact of a hemodynamic disturbance on the brain to be correlated with the changes in the aEEG background pattern. These four clinical scenarios demonstrate how simultaneous neuromonitoring with aEEG and NIRS provides important clinical information. We speculate that routine use of these combined monitoring modalities may become the future standard for neonatal neuromonitoring.